The Impacts of Shipboard Training Program on the Competence of Cadets - Andy Wahyu Hermanto; M. Imroni Mubin; Nerru Pranuta Murnaka; M. Takbir Malliongi (Jurnal Penelitian Pendidikan IPA, 2026)
Sea practice activities are carried out by cadets of the nautical and engineering study programs in order to improve knowledge and competence in the maritime field. The purpose of this study is to analyze the influence of mentors on cadet competencies, analyze the influence of environmental factors on cadet competencies and analyze the influence of learning motivation on cadet competencies. The method used in this study is quantitative. Respondents are cadets of PIP Semarang semester 7. The number of samples used is 104 people. The survey was conducted with a questionnaire via google form and using a Likert scale. The results of this study are mentors (ship crew, guardian lecturers, mentors) do not have a significant effect on cadet competencies, environmental factors do not have a significant effect on cadet competencies and cadet learning motivation has a significant effect on cadet competencies. So that the relationship between ship crew, mentors and guardian lecturers with cadets and environmental factors during sea practice can be further improved.